Pemeriksaan Coliform dan Coli Tinja pada Sumur Bor di Desa Waiheru Perumnas RT 28/RW 007 Kecamatan Baguala Kota Ambon - Arfan Ohorella (Inovasi Kesehatan Global, 2024)
To improve public health, the problem of providing clean water must be a top priority. Since water is essential for all living things, water is also very important. It requires the availability of healthy water, which includes monitoring and regulating water quality to meet human needs and life. The goal is to ensure that everyone has access to healthy drinking and clean water. Target. The aim of this research is to find out whether there are coliforms and fecal coliforms in the drilled well located on Rt 28/Rw 007, Baguala District, Ambon City. Methodology. This research is classified as descriptive research. The 6 water samples used were taken at Rt 28/Rw 007 Baguala District, Ambon City. The total population in this research is six drilled wells. All drilled well water was taken at 1 Rt/Rw and used as the resulting sample. The research results showed that fecal coliform and coli bacteria were found in drilled well water at Rt 28/Rw 007 Waiheru Perumnas Village, Baguala District, Ambon City; three drilled well water was positive for coliform bacteria, and one drilled well water was negative. Five positive borehole water also had negative coliform bacteria. Decision: According to the Republic of Indonesia Minister of Health Regulation number 32 of 2017 concerning environmental health quality standards and water health requirements for sanitation hygiene purposes, swimming pools, aqua solutions and public baths, the number of coliform bacteria is 1 and the number of coliforms is 3.